Effects of filtering of harmonics from biosonar echoes on delay acuity by big brown bats (Eptesicus fuscus) - Bates, Mary E. (Acoustical Society of America, 2010)
Big brown bats emit FM biosonar sounds containing two principal harmonics (FM1∼55–22 kHz;FM2∼105–45 kHz). To examine the role of harmonics, they were selectively filtered from stimuli in electronic-echo delay discrimination experiments. Positive stimuli were delayed by 3.16 ms (55 cm simulated target range); negative stimuli were by delayed by 3.96 ms (68 cm). This large 800-μs delay difference (nearly 14 cm) was easily discriminated for echoes containing equal-strength FM1 and FM2. Performance gradually decreased as highpass filters removed progressively larger segments from FM1. For echoes with FM2 alone, performance collapsed to chance, but performance remained good for lowpass echoes containing FM1 alone. Attenuation of FM2 by 3 dB relative to FM1 also decreased performance, but shortening electronic delay of the attenuated FM2 by 48 μs counteracted amplitude-latency trading and restored performance. Bats require the auditory representations of FM1 and FM2 to be in temporal register for high delay acuity. Misalignment of neuronal responses degrades acuity, but outright removal of FM2, leaving only FM1, causes little loss of acuity. Functional asymmetry of harmonics reflects lowpass effects from beaming and atmospheric propagation, which leave FM1 intact. It may cooperate with latency shifts to aid in suppression of clutter.